2021
DOI: 10.20411/pai.v6i1.441
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Responses to SARS-CoV-2 mRNA Vaccines Are Detectable in Saliva

Abstract: The approved Pfizer and Moderna mRNA vaccines are well known to induce serum antibody responses to the SARS-CoV-2 Spike (S)-protein. However, their abilities to elicit mucosal immune responses have not been reported. Saliva antibodies represent mucosal responses that may be relevant to how mRNA vaccines prevent oral and nasal SARS-CoV-2 transmission. Here, we describe the outcome of a cross-sectional study on a healthcare worker cohort (WELCOME-NYPH), in which we assessed whether IgM, IgG, and IgA antibodies t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
74
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 34 publications
11
74
2
Order By: Relevance
“…Recent studies have evaluated serum and mucosal tissues including saliva and nasal swabs for cellular and antibody immunity to COVID-19 and vaccination and shown that a multifaceted immune response is important for protection (26,(34)(35)(36)(37)(38)(39). Further, there is evidence that NAbs are an important correlate of protection in the immune response to SARS-CoV-2 (26,(38)(39)(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have evaluated serum and mucosal tissues including saliva and nasal swabs for cellular and antibody immunity to COVID-19 and vaccination and shown that a multifaceted immune response is important for protection (26,(34)(35)(36)(37)(38)(39). Further, there is evidence that NAbs are an important correlate of protection in the immune response to SARS-CoV-2 (26,(38)(39)(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies against the SARS-CoV-2 RBD were detectable in all 66 saliva and serum samples. Likewise, the levels of IgG in both saliva and serum remained detectable the longest (20).…”
Section: Saliva-based Elisasmentioning
confidence: 91%
“…The vaccine-induced protection observed in experimental models and in humans in phase 3 studies has not provided evidence that the vaccine prevents the possibility of infection [22,24,28,29,[83][84][85]. However, the recent identification of salivary IgA in subjects vaccinated with two doses of mRNA vaccines [86] is reassuring because, even though its protective role has not been explored, it allows us to rule out the fear of a poor IgA mucosal immune response [87].…”
Section: Covid-19 Vaccinesmentioning
confidence: 99%